NGOs in Local Governance in Bangladesh: A New Wave in Development Disclosure. (September 2015) - Baroi, Harold Sougato; Panday, Pranab Kumar
In the last decade, local governance has emerged as one of the most significant issues in development discussion. NGOs and international agencies have placed themselves in a strategic position to focus on this subject in the recent times. They are now more involved in capacitating local government institutions (LGIs) and the local community to understand roles and responsibilities and act effectively towards responsive and participatory governance. NGOs have a special place in the socio-economic development in Bangladesh, and many of the popular NGO models have been replicated in different parts of the world. In the last four decades, the operation of NGOs has seen growth and also criticisms regarding how many of these NGOs have transformed themselves from non-profit-oriented organisations to money-driven unit in Bangladesh. However, NGOs, with a change in approach—from relief and rehabilitation to community development and now right-based development—have still found themselves in an important position in Bangladesh. In the recent years, some of the prominent NGOs and international development partners have made an enormous contribution in strengthening LGIs by facilitating the process of ensuring people's participation, and transparency and accountability of the overall governing process.